University Funding Formulas: An Analysis of the Québec Reforms and Incentives - Bouchard St-Amant, Pier-André; Brabant, Alexis-Nicolas; Germain, Éric (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2020)
This paper analyzes the incentives induced by a formula to fund universities based primarily on enrolment. Using a simple game theoretical framework, we argue that inherently those formulas lower the funding per student. We argue that if the funding value differs by enrolment type, it introduces incentives to substitute enrolment where most profitable. We use these results to discuss the 2018 funding formula changes in Québec. Québec’s latest reform is an attempt to reduce substitution effects and increase graduate enrolment. We provide simulations of the reform’s redistributive effects. With the formula change, some universities have structural advantages over others. Whilst the reform, on a short-term basis, deploys a mechanism to mitigate these advantages, on a long-term basis the effect introduces a larger gap between Québec higher-education institutions.